New Approach to reduce High School Dropout Rates - Portillo-Torres, Mauricio Cristhian (2015)
From 2006 to 2014, the Ministry of Public Education of Costa Rica implemented four strategic actions to reduce high school dropout rates. The main purpose of these actions was to promote student participation and student identification with their school. Studies prepared by the Ministry of Education and the Comptroller of the Republic were revised to assess the impact of these actions. The result of these actions does not show an actual decrease in the number of students who leave high school. Therefore, a more holistic view is necessary to ensure the students’ stay. This review suggests using use the concept of student engagement and applying a three tier system-wide dropout preventive actions: universal, targeted and intensive.